Minding time : a philosophical and theoretical approach to the psychology of time - Montemayor, Carlos (Supplements to The study of time, 2013)
Minding Time: A Philosophical and Theoretical Approach to the Psychology of Time offers a theoretical account of the most fundamental kinds of time representation, drawing on philosophy, psychology, neuroscience, and biology. Recent experimental findings on creatures from bees to scrub-jays to human beings have demonstrated the complex ¿́¿ and astoundingly reliable ¿́¿ functioning of biological clocks. These clocks, Carlos Montemayor argues, make possible representations of duration that are then anchored to representations of simultaneity, and they do so independently of conscious information or representations of the self. Montemayor offers an innovative philosophical explanation of how representations of duration and simultaneity relate to the consciously experienced present moment. No theory has integrated the research on representations of simultaneity and duration. Minding Time: A Philosophical and Theoretical Approach to the Psychology of Time provides such a theory, showing that the metric constraints on time measurements are not dependent on phenomenal consciousness.